Meat products for obese people - Galenko, Oleg (My University, 2019)
According to the content of essential amino acids ham meat guinea fowl close to egg protein, and according to the content of of amino acids as valine, isoleucine, leucine, lysine, alanine, arginine, aspartic acid, glycine, glutamic acid, tyrosine surpasses it. This indicates that the cooked ham and smoked guinea fowl meat have well balanced amino acid composition, it is characterized by high biological value and can be attributed to high-grade food for the content of essential amino acids. За вмістом незамінних амінокислот шинка м'ясо цесарок близьке до яєчного білка, і за вмістом амінокислот, таких як валін, ізолейцин, лейцин, лізин, аланін, аргінін, аспарагінова кислота, гліцин, глутамінова кислота, тирозин перевершує її. Це свідчить про те, що варена і копчене м'ясо цесарок має добре збалансований амінокислотний склад, воно характеризується високою біологічною цінністю і може бути віднесене до повноцінної їжі за вмістом незамінних амінокислот.
Keywords: gerodietic; meat products; supplements; геродиєтичні; meat products; supplements; кафедра технології м’яса і м’ясних продуктів